Lysosomal acid lipase deficiency: A rare inherited dyslipidemia but potential ubiquitous factor in the development of atherosclerosis and fatty liver disease - Besler, Katrina J.; Blanchard, Valentin; Francis, Gordon A. (Frontiers in Genetics, 2022)
Lysosomal acid lipase (LAL), encoded by the gene LIPA, is the sole neutral lipid hydrolase in lysosomes, responsible for cleavage of cholesteryl esters and triglycerides into their component parts. Inherited forms of complete (Wolman Disease, WD) or partial LAL deficiency (cholesteryl ester storage disease, CESD) are fortunately rare. Recently, LAL has been identified as a cardiovascular risk gene in genome-wide association studies, though the directionality of risk conferred remains controversial. It has also been proposed that the low expression and activity of LAL in arterial smooth muscle cells (SMCs) that occurs inherently in nature is a likely determinant of the propensity of SMCs to form the majority of foam cells in atherosclerotic plaque. LAL also likely plays a potential role in fatty liver disease. This review highlights the nature of LAL gene mutations in WD and CESD, the association of LAL with prediction of cardiovascular risk from genome-wide association studies, the importance of relative LAL deficiency in SMC foam cells, and the need to further interrogate the pathophysiological impact and cell type-specific role of enhancing LAL activity as a novel treatment strategy to reduce the development and induce the regression of ischemic cardiovascular disease and fatty liver.